Edukasi Kesehatan dalam Mencegah Kecanduan Internet pada Remaja dengan Melakukan Aktivitas Fisik - Prima Dian Furqoni; Zulhaida Zulhaida; Ladin Juliawan; Ida Rahmatika; Novindri Ryalita; Ni Wayan Oktavia Anjani; Idfy Dwi Prayogo (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Problematic Internet use is the inability to control the desire to use the Internet, which is associated with psychological, social, educational and vocational problems. The internet is a place where young people can get all the information they need. Therefore, the use of the Internet by the younger generation must be directed so that they do not encounter information that is false, misleading, or even detrimental to themselves. Excessive internet use can also worsen the quality of teenagers' sleep, and teenagers may even be at risk of experiencing more serious mental health problems, such as depression. The aim of this activity is to increase knowledge about preventing internet addiction by doing physical activity. The results of the questionnaire obtained from the ASSIST questionnaire showed that of the 36 respondents there were 12 respondents (33.3%) who were addicted to smoking. Meanwhile, the Self Reporting Questionnaire (SRQ) 20 questionnaire shows that out of 36 respondents there were 8 respondents (22.2%). Internet addiction in teenagers can affect the content of their thoughts regarding the life goals they pursue